Covalent Self‐Assembly and One‐Step Photocrosslinking of Tyrosine‐Rich Oligopeptides to Form Diverse Nanostructures. Issue 24 (8th April 2016) - Min, Kyoung‐Ik; Yun, Gyeongwon; Jang, Yoonjung; Kim, Kyung‐Rok; Ko, Young Ho; Jang, Hyung‐Seok; Lee, Yoon‐Sik; Kim, Kimoon; Kim, Dong‐Pyo
Abstract: We present covalently self‐assembled peptide hollow nanocapsule and peptide lamella. These biomimetic dityrosine peptide nanostructures are synthesized by one‐step photopolymerization of a tyrosine‐rich short peptide without the aid of a template. This simple approach offers direct synthesis of fluorescent peptide nanocages and free‐standing thin films. The simple crosslinked peptide lamella films provide robust mechanical properties with an elastic modulus of approximately 30 GPa and a hardness of 740 MPa. These nanostructures also allow for the design of peptidosomes. The approach taken here represents a rare example of covalent self‐assembly of short peptides into nano‐objects, which may be useful as microcompartments and separation membranes. Abstract : Covalent self‐assembly of peptides : Direct synthesis of fluorescent peptide nanocapsules and free‐standing thin films by bioinspired one‐step photopolymerization of peptides is reported. The crosslinked peptides showed superior mechanical strength compared to non‐covalent peptides, and were used to design robust peptidosomes.